Melatonin promotes the development of sheep transgenic cloned embryos by protecting donor and recipient cells. Issue 13 (3rd July 2022) - Yao, Yujun; Yang, Ailing; Li, Guangdong; Wu, Hao; Deng, Shoulong; Yang, Hai; Ma, Wenkui; Lv, Dongying; Fu, Yao; Ji, Pengyun; Tan, Xinxing; Zhao, Wanmin; et al.
ABSTRACT: The yield efficiency of transgenic animal generation is relatively low[1 ]. To improve its efficiency has become a priority task for researchers[2 ]. Melatonin (N-acetyl-5-methoxytryptamine, MT) is a potent-free radical scavenger and antioxidant to protect mitochondria, lipids, protein and DNA from oxidative stress[3 ]. In this study, we observed that improving the quality of both donor and recipient cells by giving physiological concentration (10 −7 M) of MT significantly increase the sheep transgenic embryo development in the in vitro condition. MT promotes the donor cell viability, proliferation, efficiency of monoclonal formation and the electrotransferring efficiency of fetal fibroblast cells (FFCs). The mechanistic exploration indicates that MT has the capacity for the synchronization of cell division cycle, reduction of cellular oxidative stress, apoptosis, and the increase of mitochondrial number and function. All of these render MT's ability to increase the efficiency of animal transgenic processes such as somatic cell nuclear transfer (SCNT) and electroporation. The outcomes are the increased cleavage rate and blastocyst rate of the transgenic sheep embryos after MT treatment. These beneficial effects of MT on transgenic embryo development are worth to be tested in the in vivo condition in the future.